PENDAMPINGAN BELAJAR MEMBACA AL-QUR’AN DENGAN METODE KARIMAH PADA MASYARAKAT BABADAN BERJO NGARGOYOSO - Parwanto, Parwanto (Tahta Media Grup, 2023)
The purpose of this community service activity is to assist the community in learning to read the Qur'an using the karimah method. The number of residents who are adults but cannot read the Qur'an properly is the reason for the author to do this service. The method of service is by practicing directly reading the Karimah Book with intensive assistance. During the mentoring process the residents were very enthusiastic, the halaqoh atmosphere was very interactive through discussion and feedback. The results of the mentoring that some participants have been able to read the Qur'an properly and correctly based on direct reading practice on the Qur'an. However, it is realized that not all participants have been able to complete the Karimah Book as a whole, because some participants are elderly and the meeting is very short, so the author hopes that further activities will be held.